Impact of regulatory process on Telecom Firm Performance: Evidence from Non Parametric Approach - Sami Debbichi; Ramzi Ben Slama (Yayasan Ahmar Cendekia Indonesia, 2022)
This paper analyzes the effects of regulation, privatization, and competition on the telecommunications performance in 40 Latin American, African, and Arab countries from 1992 through 2010. By using difference-in-Difference with control variables and propensity score matching techniques, our study reveals that regulation is positively correlated with tariffs and quality. However; competition has no effect on tariffs. This result allows us to suspect the presence of collusion between competitors.